The Effect of Corporate Governance Mechanism on Intellectual Capital Disclosure of High IC-Intensive Companies in Indonesia and Malaysia - Evi Rahmawati; Naufal Fadlurrahman; Firda Shofia Azzahra (Universitas Muhammadiyah Yogyakarta, Indonesia, 2022)
Research aims: This study examines the effect of corporate governance mechanisms, such as board size, CEO duality, number of the audit committee, board gender, and family ownership, on intellectual capital disclosures.Design/Methodology/Approach: The sample study was high intellectual capital (IC)-intensive companies listed on the Indonesia Stock Exchange and Malaysia Stock during 2017-2018.Research findings: For Indonesia, the results revealed that the number of the audit committee and board size had a positive and significant effect on intellectual capital disclosures. Meanwhile, in Malaysia, the results showed that audit committees had a positive and significant effect on intellectual capital disclosures.Theoretical contribution/Originality: This study adds literature on the effect of corporate governance mechanisms on intellectual capital disclosure of high IC-intensive companies in the development of the country context.